Loss of sediments and nutrients through runoff steepness and soybean variety on portuguesa river basin - Queiroz, Manoel Moisés F. de; Santos, Ana Luca de A. dos; Gomes, Simone D. (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
There is a great concern in areas with intensive agricultural use, such as physical structure of soil, management system, pesticides application schedule and others. Those practices are associated with environmental problems that indirectly affect the life quality as runoff and other nutrients that are carried through it. This trial studied the loss of sediments, phosphorus and total nitrogen through runoff during the cycle of soybean crop, 2007/2008, in a tillage area on Portuguesa river basin, Paraná state, Paraná. The experimental design had sixteen plots with four treatments and four replications, two steepness and a green cover. The treatments were represented by T1 (conventional soybean steepness < 10 %); T2 (transgenic soybean steepness < 10 %); T3 (conventional soybean steepness > 10 %) and T4 (transgenic soybean steepness > 10 %). During the trial installation, the authors respected the steepness direction. There were eight occurrences of rainfall during the crop cycle. But, the runoff occurred only during the four first ones. The results showed that concentrations varied a lot because of the variability of drained volumes. The behavior of total nitrogen as a parameter got a good correlation with the drained volume. The parameter phosphorus obtained several concentrations despite the drained volume. Volatile solids concentrations were higher than the fixed solids ones. There was no significant effect (p ≤ 0.05) of green cover concerning the obtained results, as well as steepness.